CUSTOMER SERVICE APPLICATION IN THE MOTOR COURT GARAGE USING VISUAL BASIC 6.0 - M. Oetomo Rizky Irwanto; Yuce Yuliani, S.Kom., MMSI (Jurnal Sistem Informasi, 2009)
Along with the rapid development era, the more permsalahan facing mankind. The necessity to solve problems quickly, accurately, and efficiently, it is very necessary. Therefore the role of the computer provides an enormous impact on human life, as a means to accelerate data processing. In this study, the authors make a computerized system to process customer service at Palace Motor Repair using Microsoft Visual Basic 6.0. This system aims to replace the manual systems with new systems that have been computerized, with the hope that this new system can facilitate data processing on the Motor Palace workshops. Scientific writing is also equipped with Flow of Document (FOD), Data Flow Diagrams (DFD), Entity Relationship Diagram (ERD) and also the normalization of the application.